Tradisi Barodak Masyarakat Sumbawa Barat: Kajian Fungsi Dan Makna - Apitalia, Sri; Mahsun, Mahsun; S, Aswandikari (Pendidikan Bahasa dan Sastra, 2023)
This research aims to find out the barodak tradition of the people of West Sumbawa using a study of function and meaning. This research is a type of research that uses descriptive qualitative because this research focuses on culture. Apart from that, this research also uses qualitative ethnography because it is directly involved with the community. Data collection in this research was carried out using observation, interviews, documentation, recording and note-taking techniques. The results of this research show that there are many functions and meanings in the barodak tradition. The function study used by researchers is the function study from William R. Bascom while the meaning study comes from Carles Sanders Peirce. The functions contained in the barodak tradition include, firstly, as a tool for reflecting and projecting the dreams of its collective members, secondly as a tool for ratifying intermediaries and cultural institutions, thirdly as a tool for educating children, fourthly as a tool of coercion and monitoring to ensure norms -community norms will always be obeyed by its collective members. Meanwhile, the meaning of the barodak tradition is sign, object and interpertant. Based on the function and meaning of the barodak tradition, four symbols are taken, including, mani pengantan (bridal shower), dila malam (candle), barodak (scrub), rapancar (reddened nails). All the symbols used in the traditional barodak procession are a form of hope and prayers offered by family, relatives and the community to the prospective bride and groom so that in the future the household they build can become a household of sakinah, mawaddah and warohma, given worldly happiness and hereafter and always be blessed by the Almighty.